Hubungan Aktualisasi Diri dan Kemampuan Komunikasi dengan Adaptabilitas Karier Abad 21 Siswa SMK di Kota Malang - Devani Aulia Zulfa; Setiadi Cahyono Putro; Hari Putranto (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
The 21st century has a major impact on the world of work, where students are required to have 21st century skills. Students must be able to plan a career, be able to adapt and be able to master today's technology (21st century career adaptability) (Y). Factors that influence are self actualization (X1) and communication skills (X2). This study aims to determine: (1) Description of X1, X2, Y, (2) Relationship of X1 to Y; (3) Relationship of X2 with Y, (4) Relationship of X1 and X2 with Y. This research is an Ex Post Facto using quantitative research methods. This study uses a saturated type purposive sampling technique as many as 97 respondents. Variables X1, X2 and Y have the level of reliability in sequence are 0.903, 0.831, and 0.885. The Effective Contribution Value at X1 and X2 is 46,92% and 27.98%. The Relative Contribution Value at X1 and X2 is 63% and 37%. The conclusions of this study are (1) Positive and significant relationship between X1 and Y, X2 and Y; (2) positive and significant relationship between X1 and X2 simultaneously with Y. Keywords: 21st Century Career Adaptability, Self Actualization, Communication Skill